2020
DOI: 10.1155/2020/8347095
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogeochemistry of Surface and Ground Water in Alatening Village, Northwest Region, Cameroon

Abstract: The purpose of this study was to evaluate petrography and the quality of water for drinking purposes in Alatening, Northwest Cameroon, with respect to the World Health Organization (WHO) standards. The indigenes of the study area, as well as other dwellers in rural areas, consume water from these sources whose quality is unknown; thus, it can lead to contamination and waterborne diseases. Three springs and two streams of Alatening village were investigated in early December 2017 and late July 2018 for organole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…The other study to analyze the quality of household clean water based on people's perception, by Noeraga et al (2020), found that the water quality is inadequate for daily needs. Based study of water quality in Alatening Village, Cameroon, the fecal coliforms, as well as specific bacteria such as Enterobacter, Escherichia coli, Streptococcus, Salmonella, and Shigella, were found in all the water samples, attributable to poor hygiene (Njoyim et al, 2020). Those all-previous studies explained that critical issues in water quality are drinking water as lack of quality caused contaminant chemical, physical and biological exceed as parameter standard quality based on WHO or country regulation.…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…The other study to analyze the quality of household clean water based on people's perception, by Noeraga et al (2020), found that the water quality is inadequate for daily needs. Based study of water quality in Alatening Village, Cameroon, the fecal coliforms, as well as specific bacteria such as Enterobacter, Escherichia coli, Streptococcus, Salmonella, and Shigella, were found in all the water samples, attributable to poor hygiene (Njoyim et al, 2020). Those all-previous studies explained that critical issues in water quality are drinking water as lack of quality caused contaminant chemical, physical and biological exceed as parameter standard quality based on WHO or country regulation.…”
Section: Introductionmentioning
confidence: 95%
“…Water is good for microorganisms, like groundwater, and surface water may contain bacteria, viruses, fungi, and algae, which makes water objectionable for domestic purposes and health-threatening (Jebreen & Ghanem, 2015). Water is considered pure when colorless and free from turbidity and abnormal taste and smell (Njoyim et al, 2020;Ajith et al, 2023;Patel et al, 2023). Water is polluted when it contains microorganisms of human or animal origin, poisonous chemical substances, industrial or domestic sewage, and organic and inorganic substances (Mitiku, 2020;Al-Taai et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…The limitation of water resources is a major factor in the development of agriculture in arid and semiarid areas of the world [1,2,3]. One of the primary factors is climate change and variability that affect the potential of available water resources [4,5,6].…”
Section: Introductionmentioning
confidence: 99%